STRATEGY IN REDUCE PROBLEM FINANCING IN KOPERASI WANITA SRIKANDI, BUDURAN, SIDOARJO - Hersa Farida Qoriani (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2022)
The obstacle faced so far, especially the Koperasi Wanita Srikandi Buduran Sidoarjo, is problematic financing; not a few customers have participated in the Koperasi Wanita Srikandi. The focus of the problem raised is how to implement the 7C principle (character, capital, capacity, collateral, condition of economy, constraint, and coverage) in reducing problematic financing in the Koperasi wanita srikandi? The purpose of this study was to find out the implementation of the 7C principles in reducing problematic financing in the Koperasi Wanita Srikandi. This study uses a descriptive qualitative approach in describing most of the contents of the research where the type of research used is phenomenological which is thus also categorized as field research. The results of this study state that the implementation of the application of the 7 C principles in analyzing financing applications can minimize the risk of financing even though it turns out that financing is still substandard to jam but in small numbers, and the principle aspect Character become more dominant than other principles